Santa Bruce - Higgins, Ryan T (Los Angeles Disney/Hyperion, 2018)
Grumpy and cold when his forest friends insist he stay awake to celebrate Christmas, Bruce the bear, wearing his long underwear and warm hat, is mistaken for Santa by the youngest forest creatures.
Keywords: Santa Claus -- Juvenile fiction; Santa Claus -- Fiction; Christmas stories; Bears -- Juvenile fiction; Forest animals -- Juvenile fiction; Attitude (Psychology) -- Juvenile fiction; Christmas -- Fiction; Bears -- Fiction; Forest animals -- Fiction; Attitude (Psychology) -- Fiction; Humorous Stories